Biochemical Correlates of the Circadian Rhythm in Photosynthesis in Phaseolus vulgaris - Fredeen, Arthur L. (1991)
A circadian rhythm in photosynthesis occurs in Phaseolus vulgaris after transfer from a natural or artificial light:dark cycle to constant light. The rhythm in photosynthesis persists even when intercellular CO(2) partial pressure is held constant, demonstrating that the rhythm in photosynthesis is not entirely due to stomatal control over the diffusion of CO(2). Experiments were conducted to attempt to elucidate biochemical correlates with the circadian rhythm in photosynthesis. Plants were entrained to a 12-hour-day:12-hour-night light regimen and then monitored or sampled during a subsequent period of constant light. We observed circadian oscillations in ribulose-1,5-bisphosphate (RuBP) levels, and to a lesser extent in phosphoglyceric acid (PGA) levels, that closely paralleled oscillations in photosynthesis. However, the enzyme activity and activation state of the enzyme responsible for the conversion of RuBP to PGA, ribulose-1,5-bisphosphate carboxylase/oxygenase, showed no discernible circadian oscillation. Hence, we examined the possibility of circadian effects on RuBP regeneration. Neither ribulose-5-phosphate kinase activity nor the level of ATP fluctuated in constant light. Oscillations in triose-phosphate levels were out of phase with those observed for RuBP and PGA.